2017
DOI: 10.1371/journal.pone.0175052
|View full text |Cite
|
Sign up to set email alerts
|

Association of the IL-1RN variable number of tandem repeat polymorphism and Helicobacter pylori infection: A meta-analysis

Abstract: The aim of this study was to clarify the association of IL-1RN variable number of tandem repeat (VNTR) polymorphism and H. pylori infection. We performed a meta-analysis of studies retrieved by systematic searches of Pubmed, Embase and the Cochrane Library. Data were analyzed with STATA 13.1 using pooled odds ratios (ORs) with 95% confidence intervals (CIs). A total of 18 studies were included in our meta-analysis, and IL-1RN VNTR was found to be significantly associated with H. pylori infection in the compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In this case-control study, we calculated the association of IL1RN polymorphisms with the risk of esophageal IL1RN is a member of the IL-1 cytokine family that modulates a variety of IL-1-related immune and inflammatory responses. Numerous lines of evidence have shown that IL1RN plays a key role in the regulation of cancer pathogenesis and chronic inflammation [20][21][22]. We obtained the expression data for IL1RN from the GEPIA online database (http://gepia.cancer-pku.cn/) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case-control study, we calculated the association of IL1RN polymorphisms with the risk of esophageal IL1RN is a member of the IL-1 cytokine family that modulates a variety of IL-1-related immune and inflammatory responses. Numerous lines of evidence have shown that IL1RN plays a key role in the regulation of cancer pathogenesis and chronic inflammation [20][21][22]. We obtained the expression data for IL1RN from the GEPIA online database (http://gepia.cancer-pku.cn/) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the previous literature has illustrated that the inflammatory response after Helicobacter pylori infection has been linked to the IL-1 gene cluster ( IL-1A , IL-1B , and IL1RN ). A meta-analysis of H. pylori infection performed by Zhang et al [21] demonstrated that IL1RN polymorphisms may increase the risk of H. pylori infection, especially in Asians. Therefore, we can infer that IL1RN polymorphisms may be associated with the risk of esophageal cancer with H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…(31, 38, 47, 48) Since 2000 when Omer et al ., reported the first significant association between gastric cancer risk and polymorphism in the genes IL-1B and IL-1RN among Scottish and Polish patients, (31) a lot of studies from different ethnic groups and populations have pointed out this relation as well. (32, 49, 50) Unfortunately, to the best of our knowledge, no data regarding these polymorphisms are available in Sudan where gastric cancer, according to GLOBOCAN 2018, represents one of the top causing death among cancers with about 686 cases per year and 2.7 % mortality rate. (51) However, most of the studies have observed this association with an IL-1RN 2/2 homozygous genotype (31, 38, 48) but we found this association with a heterozygous genotype ( IL-1RN 2/L) with OR=12.83 (95% CI = 1.261-130.6, P = 0.0302) which is consistent with other studies conducted in Italy, (47, 52) Brazil, (53) Taiwan, (54) China, (55) Turkey (39) and Arabic population (Omani and Algerian) (56, 57) that found the same association of gastric cancer with a IL-1RN 2/L heterozygous genotype.…”
Section: Discussionmentioning
confidence: 99%
“…(13, 30, 31) The most intensively studied IL-1RN polymorphism connected to susceptibility to H. pylori infection and gastric cancer outcome is a penta-allelic 86-bp VNTR (variable number of tandem repeats) polymorphism that is located in intron 2. (12, 32-34) The most typical variants contains four repeats named allele IL1RN*1 and variants with 2 repeats (allele IL1RN*2 ). While other alleles, 3 repeats (allele IL1RN*4 ), 5 repeats ( allele IL1RN*3 ) and 6 repeats ( allele IL1RN*5 ), (35) occur at a combined frequency of <5%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation